Fermented soil amendments made from stabilized biosolids and fly ash improve maize (Zea mays L.) nutrition and growth - Karla E. Cortés-Tello; Pablo F Jaramillo-López (International Journal of Recycling of Organic Waste in Agriculture)
Purpose To evaluate the feasibility of using biosolids and fly ash, processed through the Bokashi fermentation process, as growth promoters of maize. These two components were included because they are generated in large amounts and represent an environmental problem all over the world. Additionally, these materials have high concentrations of nutrients, but they have not been widely used because they also contain traces of heavy metals. Methods Components of regular Bokashi are as follows: soil, cow manure, chopped corn stalks, wheat bran, yeast, crushed charcoal, water and brown sugar. For this research, cow manure was replaced with biosolids, and charcoal was replaced with fly ash. The materials were mixed, inoculated with Saccharomyces cerevisiae and allowed to be fermented until the temperature stabilized. The maize plants were grown in four treatments: Bokashi with biosolids and fly ash, Bokashi with cow manure, chemical fertilizer and an unamended control. Results The plants grown in the Bokashi with biosolids and fly ash (BBFA) treatment had the highest aerial biomass (49.71 g), total biomass (69.82 g), N concentration (242 % higher than the control) and P concentration (94% higher than the control). Cadmium and lead concentrations were below the detection limits both in the soil amendments and in the tissue of maize plants. Conclusion Biosolids and fly ash processed by the Bokashi technique resulted in improved nutrition and growth of the maize plants. Through Bokashi fermentation, biosolids and fly ash can be safely used in agricultural or forestry applications.